Lvov and Sandomir Offensive Operation: the Look 70 Years - V. B. Makovskiy (MGIMO University Press, 2015)
Successful advances of Soviet troops in Belarus created in the middle of July 1944 favorable conditions for large-scale operations on the southern flank of the Soviet-German front to complete the liberation of Ukraine and Moldova, driving Romania, Hungary, Bulgaria out of war, and driving the enemy from Czechoslovakia. During the Soviet offensive in Belorussia 1st Ukrainian Front began operation in the Lvov direction. The operation, which was later called the Lvov-Sandomierz, turned into a major offensive of more than 400 km and lasted from July 13 to August 29, 1944. The Soviet Supreme Command was seeking to crush Army Group "Northern Ukraine", liberate Western Ukraine and take the war to the south east Poland. Operations were carried out by 1st Ukrainian Front in close cooperation with the Soviet troops operating in the Belarusian direction. It was closely linked to the southern wing of the Soviet-German front, a series of successive and simultaneous front offensive operations, including operations by groups of fronts, united by a common concept and plan, such as Lvov-Sandomierz, Iasi-Kishenёvskaya, East Carpathian.